30.2k views
0 votes
Solve the system.
x + y - z = 17
y +z = 1
z = -3

Solve the system. x + y - z = 17 y +z = 1 z = -3-example-1

2 Answers

2 votes

Answer:

(10,4,-3)

Explanation:

(x,y,z)

z= -3 given

y+z = 1 (equation 2)

y-3 =1

y=4 (solve 2 after substation)

eq #1 : x + 4 - (-3) = 17

x+4+ 3 = 17

x+ 7 = 17

x=10

(10,4,-3)

User AlexP
by
6.3k points
5 votes

Answer:

(10, 4, -3)

Explanation:

z = -3

y + z = 1

y - 3 = 1

y = 4

x + y - z = 17

x + 4 - -3 = 17

x + 4 + 3 = 17

x + 7 = 17

x = 10

(10, 4, -3)

User Galloper
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.